Numerical solution of heat-conduction problems on a semi-infinite strip with nonlinear localized flow sources - Koleva, Miglena (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2009)
We consider semi-linear heat problems on a semi-infinite interval. They model systems of temperature regulation in isotropic media with non-uniform source terms which can provide cooling or heating effects. Numerical method for overcoming the nonlinearities in the equation and boundary conditions as well as the unbounded domain is discussed.